2019
DOI: 10.3389/fimmu.2019.02109
|View full text |Cite
|
Sign up to set email alerts
|

Toward T Cell-Mediated Control or Elimination of HIV Reservoirs: Lessons From Cancer Immunology

Abstract: As the AIDS epidemic unfolded, the appearance of opportunistic infections in at-risk persons provided clues to the underlying problem: a dramatic defect in cell-mediated immunity associated with infection and depletion of CD4+ T lymphocytes. Moreover, the emergence of HIV-associated malignancies in these same individuals was a clear indication of the significant role effective cellular immunity plays in combating cancers. As research in the HIV field progressed, advances included the first demonstration of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
40
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(42 citation statements)
references
References 205 publications
(210 reference statements)
0
40
0
Order By: Relevance
“…Within the population of multimer+ HIV-specific CD8+ T cells, we found that TCF-1 expression was associated with patterns of phenotypic marker expression typically found in central memory CD8+ T cells, with a positive correlation between TCF-1 and CD127 expression (Spearman correlation, r=0.64, p<0.0001), and a negative correlation between TCF-1 and 10 Granzyme B (r=-0.64, p<0.001), and T-bet expression (r=-0.53, p<0.001), both across the whole cohort and specifically within HIV-specific CD8+ T cells isolated from controllers ( Fig. 2D).…”
Section: Tcf-1-expressing Hiv-specific Cd8+ T Cells Are Phenotypicallmentioning
confidence: 76%
See 2 more Smart Citations
“…Within the population of multimer+ HIV-specific CD8+ T cells, we found that TCF-1 expression was associated with patterns of phenotypic marker expression typically found in central memory CD8+ T cells, with a positive correlation between TCF-1 and CD127 expression (Spearman correlation, r=0.64, p<0.0001), and a negative correlation between TCF-1 and 10 Granzyme B (r=-0.64, p<0.001), and T-bet expression (r=-0.53, p<0.001), both across the whole cohort and specifically within HIV-specific CD8+ T cells isolated from controllers ( Fig. 2D).…”
Section: Tcf-1-expressing Hiv-specific Cd8+ T Cells Are Phenotypicallmentioning
confidence: 76%
“…The goal of many immune-based strategies that aim to enhance the control of HIV is to elicit functional, non-exhausted, and durable HIV-specific CD8+ T cells that have the stem-like memory T cell capacity to rapidly expand into secondary effector cells that can kill HIV-infected cells (10,12). We hypothesized that TCF-1, a Wnt signaling transcription factor known to regulate T cell "stemness" in several other contexts, might also regulate the expansion capacity of HIVspecific CD8+ T cells.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Alternatively, ZFP-362 could be used to induce sustained expression of HIV to allow for or enhance chimeric antigen T cell (CAR) targeting of infected cells. Notably, the lack of HIV antigen has proven problematic for developing robust anti-HIV CARs [41,42]. However, for either of these approaches to prove viable, the issue of delivery remains to be solved.…”
Section: Discussionmentioning
confidence: 99%
“…Chronic viral infection and cancer are pathological conditions dominated by chronic inflammation and an insufficient antigen clearance. The consequence is a difficult construction in HIV patients of a functional anti-cancer immune response, with T cells becoming exhausted for a high acquired expression of different negative check-point receptors [71] (Figure 2).…”
Section: Immunotherapymentioning
confidence: 99%